Comparative genomics analysis of pKF3-94 in Klebsiella pneumoniae reveals plasmid compatibility and horizontal gene transfer - Ying, Jianchao; Wu, Songquan; Zhang, Kaibo; Wang, Ziqiang; Zhu, Wen; Zhu, Mei; Zhang, Ying; Cheng, Cong; Wang, Huifeng; Tou, Huifen; Zhu, Chuanxin; Li, Peizhen; et al. (Frontiers in Microbiology, 2015)
In order to get insights into plasmid evolution and the dissemination of multidrug resistance, we performed extensive comparative genomics analyses of the Klebsiella pneumoniae plasmid pKF3-94 and some of its related plasmids. pKF3-94 is one of three plasmids isolated from the K. pneumoniae strain KF3. Of the 144 putative genes it harbors, 69 can be functionally assigned to be involved in transfer conjugation, transfer leading, antimicrobial resistance, transposon function and plasmid replication. Comparison of plasmid replicon sequence types revealed that pKF3-94 carries two replicons that are distinct from those carried on the two sibling K. pneumonia plasmids pKF3-70 and pKF3-140, thereby allowing pKF3-94 to coexist with these latter plasmids in the same host cell. Comparative genomics analyses further showed that pKF3-94 is more similar to plasmids pK1HV and pC15-k, which were isolated from different K. pneumonia strains, than to pKF3-70 and pKF3-140. Interestingly, pK1HV contains a unique 49 kb region rich in mobile genetic elements and drug resistance genes, while pKF3-94 and pC15-k share a 15 kb homology region partitioned into a region rich in drug resistance genes and one containing a replicon. It is conceivable, therefore, that pK1HV and pC15-k have both arisen from a common pKF3-94-like plasmid. The comparisons lend further support for the role horizontal gene transfer plays in genome evolution and in the dissemination of genetic elements including drug resistance genes.